ATRT-40. IMPACT OF MOLECULAR SUBTYPES ON TREATMENT OUTCOMES IN RHABDOID TUMORS - A REPORT FROM THE RARE TUMOR CONSORTIUM. Issue 2 (22nd June 2018) - Ho, Ben; Fonseca, Adriana; Al-Karmi, Salma; Margol, Ashley; Yao, Fupan; Cheng, Sylvia; Grant, Ronald; Handsford, Jordan; Gupta, Abha; Vasiljevic, Alexandre; Pawel, Bruce; Jabado, Nada; et al.
Abstract: BACKGROUND: Rhabdoid Tumors (RTs) are rare heritable cancers with bi-allelic SMARCB1 /A4 alterations, arising in the brain (Atypical Teratoid/Rhabdoid Tumors/ATRTs) and in various extra-cranial locations (Malignant Rhabdoid Tumors/MRTs). Recent studies uncovered molecular sub-types of ATRTs and MRTs, however, the molecular relationship and clinico-pathologic implications of MRTs and ATRTs sub-types remain unclear. METHODS: To inform clinical understanding of ATRTs and MRTs, 450/850K methylation array profiles generated from 202 ATRTs and 57 MRTs were used to define molecular categories of ATRTs/MRTs and examine their clinical significance. RESULTS: ATRTs segregated into 3 known molecular subgroups, group 1/SHH (n=87), group 2A/TYR (n=69), group 2B/MYC (n= 46); 13 and 44 MRTs respectively segregated with group 2A/TYR and 2B/MYC ATRTs. Median patient age was 19.1 months for group 1/SHH, 12.3 months for group 2A/TYR and 22.3 months for group 2B/MYC Rhabdoid tumors. Complete clinical information and treatment information available for 162 patients (n=125 ATRTs and n=37 MRTs), indicated only 65 patients received a combined chemo-radiation therapy. 24-month PFS was 30%, 38% and 28% and the 24-month OS was 43%, 48% and 43% for subgroups 1/SHH, 2A/TYR and 2B/MYC tumors respectively. CONCLUSION: MRT and ATRT comprise a biological spectrum with overlapping molecular features. Clinicopathologic analysis suggest ATRT/MRT molecular subtypes have different therapeutic response to chemo-radiotherapeutic regimens.